Conical nano-structure arrays of Platinum cathode catalyst for enhanced cell performance in PEMFC (proton exchange membrane fuel cell). (October 2015) - Khan, Aziz; Nath, Bhabesh Kumar; Chutia, Joyanti
Abstract: Conical nanostructure arrays of Pt (Platinum) as cathode catalyst are developed using a novel integrated plasma sputtering technique. The integration method involves successive deposition of Pt catalyst arrays one upon another maintaining a uniform time gap. Deposition by integrated approach results in the formation of dense arrays of Pt nanostructure as compared to continuous deposition. These high number density integrated arrays with low Pt loading of 0.10 mg cm −2 at the cathode provide enhanced performance compared to non-integrated cathode catalyst prepared by continuous deposition and standard commercial electrodes with Pt loadings of 1 mg cm −2 . The performance is compared on the basis of polarization curve measurements and the calculated power density values. PEM fuel cell with dual integrated cathode showed an improved power density of 0.90 W cm −2, which is higher than continuously deposited cathode catalyst with maximum power density of 0.67 W cm −2 for the same Pt loading of 0.10 mg cm −2 . Highlights: Conical nanostructures with high number density are prepared by a novel integrated deposition technique. Electrode with such catalyst shows maximum performance of 0.9 W cm −2 . Integrated catalyst performs better than continuously prepared nanostructure catalyst.